The diagnostic role of emotions in feminist philosophy - Valentina Bortolami (Frontiers in Psychology)
The article explores feminist phenomenological and epistemological literature to investigate the meaning of the double ontological shock, i.e., the experience of intuiting that reality differs from appearances without being able to clearly articulate what is really happening, which is relevant not only for feminists but also more generally for those who wish to reflect on the diagnostic role of emotions. The analysis of the double ontological shock supports the idea that emotions are a primary source of motivation and action orientation. This is particularly relevant in relation to situations of oppression, where emotions clearly express their diagnostic and world-disclosing nature.